Pemberdayaan Masyarakat Dalam Upaya Pelestarian Ekosistem Pesisir Dan Hutan Mangrove Manggar - Indriawati, Prita; Retnowaty, Retnowaty (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
The purpose of this Community Service (CS) is to provide an understanding of the function of the mangrove forests that have various benefits for the preservation of coastal ecosystems and clean up inorganic waste in the coastal areas. The method of community service was lecturing, demonstration, counseling and interview. The CS results were high awareness of the community to do the maintenance of the former pond land and garbage in the watershed and lastly mangrove trees can grow well. Suggestions for further CS is the need to make a proposal for sponsorship so that sustainability of these activities will occur.Keywords: community empowerment, coastal ecosystem, mangroveÂ